2011
DOI: 10.1001/archoto.2011.194
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Mediated Angiogenesis in Thyroid Tumor Microenvironment Is Mediated Through VEGF Signaling Pathways

Abstract: Our data provide evidence that estrogen can induce a proangiogenic endothelial cell phenotype in the thyroid tumor microenvironment through ER and VEGF signaling. Our findings suggest that the effect of antiestrogenic therapy targeting tumor angiogenesis can be enhanced through VEGF inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 14 publications
(26 reference statements)
0
23
0
Order By: Relevance
“…Additionally, estrogen stimulation may lead to an increased metastatic phenotype (55), possibly through induction of matrix metalloproteinase activity (56). Furthermore, in cell lines, estrogen may promote thyroid cancer cell migration and invasion and angiogenesis through vascular endothelial growth factor pathways (57). …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, estrogen stimulation may lead to an increased metastatic phenotype (55), possibly through induction of matrix metalloproteinase activity (56). Furthermore, in cell lines, estrogen may promote thyroid cancer cell migration and invasion and angiogenesis through vascular endothelial growth factor pathways (57). …”
Section: Resultsmentioning
confidence: 99%
“…In this study, we found that both the positive percentage and total score of VEGF expression were significantly decreased in female PTC patients of reproductive age with exclusively nuclear ERβ1 expression as compared with those with extranuclear localization of ERβ1, suggesting that estrogen may suppress VEGF expression through genomic actions mediated by ERβ1 localized to the nuclei of PTC cells. It has been reported that a follicular thyroid cancer cell line, ML-1, secreted more VEGF after estrogen stimulation, likely as a result of ER signaling [9]. In an animal model of ischemic stroke, ERβ contributed to the reduction of vasogenic edema via the inhibition of VEGF production [58].…”
Section: Discussionmentioning
confidence: 99%
“…VEGF has the capacity to induce angiogenesis by detachment of quiescent endothelial cells from their parental vessels followed by migration of the cells into the neighboring stroma (Krock et al 2011). In vitro thyroid cancer cells secreted VEGF in response to estrogen treatment (Kamat et al 2011). Incubation of human umbilical vein endothelial cells with a conditioned medium from estrogen-treated cancer cells resulted in angiogenesis-associated events such as tubulogenesis and migration.…”
Section: Estrogen and Angiogenesis In Thyroid Cancermentioning
confidence: 99%